2020
DOI: 10.6007/ijarafms/v10-i2/7371
|View full text |Cite
|
Sign up to set email alerts
|

Financial Literacy on Business Performance: The Moderating Effect of Religiosity Among SMEs In Sumatera, Indonesia

Abstract: Business performance represents how well the company can make use of business assets and generate receivable. Business performance is a result of company activities or investments over a given period. It is a specific business goal achievement measured against standards, completeness, and costs. The business performance was the result of corporate strategies employed to achieve market-oriented. In the years between , the Enterprise Survey (2015 has conducted a financial survey of Indonesian private sector/micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 37 publications
1
9
1
Order By: Relevance
“…They will be taking their money for saving rather than for pleasure or buying something unnecessary. The research results also support the above statement by Desiyanti & Kassim (2020), who state that religiosity can strengthen the influence of financial literacy and business performance. From the description above, the following hypothesis is obtained: H4: Religiosity can moderate the influence of financial literacy on consumption behavior Lifestyle is directly related to religion which is part of the culture that can shape a person's behavior.…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…They will be taking their money for saving rather than for pleasure or buying something unnecessary. The research results also support the above statement by Desiyanti & Kassim (2020), who state that religiosity can strengthen the influence of financial literacy and business performance. From the description above, the following hypothesis is obtained: H4: Religiosity can moderate the influence of financial literacy on consumption behavior Lifestyle is directly related to religion which is part of the culture that can shape a person's behavior.…”
Section: Introductionsupporting
confidence: 85%
“…Because financial literacy is an essential aspect of human life, a person must have good financial literacy to improve his consumption behavior regardless of whether the person is religious or not. The results of the above study are not from the research by Desiyanti & Kassim (2020), whose results state that religiosity can strengthen the influence of financial literacy and business performance.…”
Section: Hypothesis Testing Resultsmentioning
confidence: 61%
“…It may foster buyers' confidence that the firms have concern on the quality standards, enhance the corporate reputation and cares about the community and environmental welfares. Previous studies also confirmed that CSR practice is important as a sustainable strategy to growth and compete longer in the business (Desiyanti & Kassim, 2020;Ghadas et al, 2018;Samuel et al, 2011).…”
Section: Resultsmentioning
confidence: 62%
“…The finding from this study also has proved that managers' religiosity has relationship with CSR practice. Religious orientation has a strong influence on business success (Alharbi et al, 2021;Desiyanti & Kassim, 2020). Firms that incorporate the Islamic ethical values such as truthfulness, tolerance, firmness and fairness are more encouraged to sacrifice, give up and spend their wealth on the needy society and community, while expected reward only from Allah.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation